2012
DOI: 10.1371/journal.pone.0050840
|View full text |Cite
|
Sign up to set email alerts
|

“Freshwater Killer Whales”: Beaching Behavior of an Alien Fish to Hunt Land Birds

Abstract: The behavioral strategies developed by predators to capture and kill their prey are fascinating, notably for predators that forage for prey at, or beyond, the boundaries of their ecosystem. We report here the occurrence of a beaching behavior used by an alien and large-bodied freshwater predatory fish (Silurus glanis) to capture birds on land (i.e. pigeons, Columbia livia). Among a total of 45 beaching behaviors observed and filmed, 28% were successful in bird capture. Stable isotope analyses (δ13C and δ15N) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 27 publications
2
63
0
4
Order By: Relevance
“…Boulêtreau et al (2011) observed such a phenomenon in the Rhone River, but the cause of their behaviour was unclear, and no juveniles participated. Recently, some temporary catfish aggregations connected to their predatory behaviour have also been observed (Cucherousset et al, 2012). In our case, the tracked individuals displayed site fidelity at first.…”
Section: Id -Identification Number Of Individualsupporting
confidence: 56%
“…Boulêtreau et al (2011) observed such a phenomenon in the Rhone River, but the cause of their behaviour was unclear, and no juveniles participated. Recently, some temporary catfish aggregations connected to their predatory behaviour have also been observed (Cucherousset et al, 2012). In our case, the tracked individuals displayed site fidelity at first.…”
Section: Id -Identification Number Of Individualsupporting
confidence: 56%
“…notes de recherche R. Boure, M. Lefebvre L e 5 décembre 2012, la revue scientifique internationale de référence en ligne et en libre accès Plos one publie l'article d'une équipe de chercheurs toulousains (Coucherousset et al, 2012) 1 révélant, d'une part, que des silures introduits dans le Tarn -rivière du Sud de la France -attaquent des pigeons sur les berges en s'échouant selon la technique du beaching utilisée par d'autres espèces et, d'autre part, que le pigeon est devenu l'élément essentiel du régime alimentaire de certains silures. Aussitôt, « la Toile s'enflamme » -selon l'expression désormais médiatiquement consacrée -au-delà du seul champ scientifique, au grand étonnement de l'équipe de recherche 2 , peu habituée à ce phénomène que d'aucuns nomment « buzz » ou « emballement médiatique ».…”
Section: Quand Les Silures Attaquent Les Pigeonsunclassified
“…2 L'origine de notre article est une demande des auteurs de la publication (Coucherousset et al, 2012) adressée au Laboratoire d'études et de recherches appliquées en sciences sociales (lerass) en décembre 2012. Ils souhaitaient comprendre une situation pour eux inédite et qu'ils n'avaient pas concrètement provoquée puisque leurs contacts avec les médias furent postérieurs au « buzz » (entretiens).…”
Section: L'équipe Rassemble Des Chercheurs Relevant Du Laboratoire éVunclassified
See 2 more Smart Citations